Augmentation Strategies following the Microfracture Technique for Repair of Focal Chondral Defects - Strauss, Eric J. (SAGE Publications, 2010)
The operative management of focal chondral lesions continues to be problematic for the treating orthopedic surgeon secondary to the limited regenerative capacity of articular cartilage. Although many treatment options are currently available, none fulfills the criteria for an ideal repair solution, including a hyaline repair tissue that completely fills the defect and integrates well with the surrounding normal cartilage. The microfracture technique is an often-utilized, first-line treatment modality for chondral lesions within the knee, resulting in the formation of a fibrocartilaginous repair tissue with inferior biochemical and biomechanical properties compared to normal hyaline cartilage. Although symptomatic improvement has been shown in the short term, concerns about the durability and longevity of the fibrocartilaginous repair have been raised. In response, a number of strategies and techniques for augmentation of the first-generation microfracture procedure have been introduced in an effort to improve repair tissue characteristics and reduce long-term deterioration. Recent experimental approaches utilize modern tissue-engineering technologies including local supplementation of chondrogenic growth factors, hyaluronic acid, or cytokine modulation. Other second-generation microfracture-based techniques use different types of scaffold-guided in situ chondroinduction. The current article presents a comprehensive overview of both the experimental and early clinical results of these developing microfracture augmentation techniques.